Analisis Klasifikasi Diagnosa Penyakit Diabetes Melitus Berdasarkan Komparasi Algoritma Supervised Learning - Siridion, Sherly Taurin; Siregar, Bakti (Al Makki Publisher, 2024)
Diabetes mellitus is a serious health problem that threatens various age groups, including children, teenagers, and adults. In 2021, the mortality rate due to diabetes mellitus reached alarming levels, making it a global threat, especially in Indonesia, where the number of patients reached 19.5 million. Efforts to address diabetes mellitus include early prediction of the disease's risk in patients, and machine learning approaches have shown potential in this regard. This study employs a quantitative method by utilizing secondary data from the UC Irvine Machine Learning Repository titled